THE ROLE OF OXIDATIVE STRESS IN THE DEVELOPMENT OF ENDOMETRIOSIS - Shahnoza Asqaraliyeva (Web of Journals Publishing, 2025)
Endometriosis is a complex gynecological disorder that affects female reproductive health, with hormonal, immunological, and inflammatory components involved in its pathogenesis. In recent years, increasing attention has been given to the role of oxidative stress in the progression of this disease. Oxidative stress results from an imbalance between reactive oxygen species (ROS) and the body’s antioxidant defenses, leading to damage at the cellular level including lipids, proteins, mitochondria, and DNA. These alterations contribute to chronic inflammation, angiogenesis, immune dysfunction, and abnormal tissue proliferation seen in endometriosis. This article examines the clinical and molecular aspects of oxidative stress in the development of endometriosis, focusing particularly on markers such as interleukin-6 (IL-6) and phospholipase A2 (PLA2). The results of our study indicate that the addition of phytotherapeutic agents to standard hormonal therapy improves both clinical symptoms and biochemical markers. Notably, antioxidant-based integrative treatment significantly reduced pain (VAS scores), lesion size, and inflammatory markers (IL-6, PLA2), demonstrating higher effectiveness compared to hormonal monotherapy. These findings suggest that targeting oxidative stress may be a promising strategy to enhance conservative management of endometriosis.
Keywords: Endometriosis, oxidative stress, antioxidants, reactive oxygen species, IL-6, PLA2, phytotherapy, pathogenesis.